2022
DOI: 10.3389/fcimb.2022.857570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exosomes Derived From Helicobacter pylori Outer Membrane Vesicle-Infected Hepatocytes on Hepatic Stellate Cell Activation and Liver Fibrosis Induction

Abstract: Liver fibrosis is a multifactorial disease with microbial and non-microbial causes. In recent years, Helicobacter pylori infection has been thought to play a critical role in some extra-gastrointestinal manifestations especially liver disorders. Outer membrane vesicles (OMVs) are one of the most important discussed H. pylori virulence factors. In the current study, four different clinical strains of H. pylori were collected and their OMVs were purified using ultra-centrifugation. To investigate their effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…We found that LDEVs can reduce Collagen I/III and α-SMA expression in HFBs, promote wound healing and inhibit scar formation. The researchers found that outer membrane vesicles (OMVs) derived from Helicobacter pylori -derived have a probable role in liver fibrosis progression [ 35 ]. Akkermansia muciniphila -secreted EVs can inhibit the expression of liver fibrosis markers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that LDEVs can reduce Collagen I/III and α-SMA expression in HFBs, promote wound healing and inhibit scar formation. The researchers found that outer membrane vesicles (OMVs) derived from Helicobacter pylori -derived have a probable role in liver fibrosis progression [ 35 ]. Akkermansia muciniphila -secreted EVs can inhibit the expression of liver fibrosis markers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zahmatkesh et al. demonstrated that Exosomes derived from hepatocytes infected with helicobacter pylori outer membrane vesicle can lead to overexpression of HSC activation markers and fibrosis markers, suggesting a possible role in HSC activation and LF progression ( 42 ). Dai et al.…”
Section: Exosomes In Lf Pathogenesismentioning
confidence: 99%
“…During hepatitis B virus (HBV) infection, exosomes derived from HBV-infected hepatocytes promote HSC activation and LF in mice. Among them, the exosomal miR-222 could enhance HSC activation by inhibiting transferrin receptor (TFRC)-induced HSC iron death (39). Exosomes from hepatitis C virus (HCV)infected hepatocytes can also induce HSC activation.…”
Section: Exosomes Are Involved In the Activation Of Hscs In Lfmentioning
confidence: 99%
“…Currently, it is known that H. pylori infection is closely related to a variety of gastrointestinal/extragastrointestinal diseases, including chronic superficial gastritis (CSG), chronic atrophic gastritis (CAG), intestinal metaplasia (IM), dysplasia, gastric cancer, liver cirrhosis, etc. [ 3 , 4 , 5 ]. However, host–microbe interactions behind these diseases (especially stomach cancer) remain poorly understood [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 , 5 ]. However, host–microbe interactions behind these diseases (especially stomach cancer) remain poorly understood [ 3 , 4 , 5 ]. This issue has been hindering the development of preventive and therapeutic strategies for these diseases.…”
Section: Introductionmentioning
confidence: 99%